2014
DOI: 10.1126/science.1257147
|View full text |Cite
|
Sign up to set email alerts
|

Enteric bacteria promote human and mouse norovirus infection of B cells

Abstract: The cell tropism of human noroviruses and the development of an in vitro infection model remain elusive. Although susceptibility to individual human norovirus strains correlates with an individual’s histo-blood group antigen (HBGA) profile, the biological basis of this restriction is unknown. We demonstrate that human and mouse noroviruses infected B cells in vitro and likely in vivo. Human norovirus infection of B cells required the presence of HBGA-expressing enteric bacteria. Furthermore, mouse norovirus re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
806
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 719 publications
(866 citation statements)
references
References 43 publications
24
806
3
1
Order By: Relevance
“…1c), respectively, further indicates that virus binding to the tubes was not an issue in our experiments. Furthermore, in correlation with our observations, a stimulative effect of HBGAs on G2.4 human NoV infectivity was recently also reported (Jones et al, 2014).…”
Section: Synthetic Oligosaccharidessupporting
confidence: 76%
“…1c), respectively, further indicates that virus binding to the tubes was not an issue in our experiments. Furthermore, in correlation with our observations, a stimulative effect of HBGAs on G2.4 human NoV infectivity was recently also reported (Jones et al, 2014).…”
Section: Synthetic Oligosaccharidessupporting
confidence: 76%
“…No robust cell culture system is available for HuNoV although norovirus RNA is infectious in mammalian cells and a recent study showed the development of an in vitro infection model for 2 human noroviruses in human B cells (Duizer et al 2004b;Malik et al 2005;Guix et al 2007;Jones et al 2014). Due to the complexity and the specific requirements for this new in vitro cell culture system for HuNoV, the use of viral surrogates is still required.…”
Section: Introductionmentioning
confidence: 99%
“…129 Recent developments have established evidence demonstrating the ability of MuNoVs to persistently infect mouse B cell lines in vitro. 71 The authors also tested the ability of GII.4 isolate to infect human B cell line; the former replicated efficiently in B cells and produced new infectious virus particles. The tropism of human and murine NoV to B cells is a breakthrough for the development of human NoV infection and vaccine model.…”
Section: Human Trialsmentioning
confidence: 99%
“…Recent developments have however established evidence demonstrating the ability of MuNoVs to persistently infect mouse B cell lines in vitro. 71 VLPs are immunogenic and able to enhance uptake by antigen-presenting cells (APCs) and to stimulate effector cells. 72 VLPs are similar to the wild virus with strain-and group-specific antigenic determinants.…”
Section: Immune Correlates Of Protectionmentioning
confidence: 99%